Effects of Different Combinations of Er:YAG Laser-Adhesives on Enamel Demineralization and Bracket Bond Strength - Cokakoglu, Serpil; Nalcaci, Ruhi; Usumez, Serdar; Malkoc, Siddik (My University, 2016)
Objective: The purpose of this study was to investigate the demineralization around brackets and shear bond strength (SBS) of brackets bonded to Er:YAG laser-irradiated enamel at different power settings with various adhesive systems combinations. Methods: A total of 108 premolar teeth were used in this study. Teeth were assigned into three groups according to the etching procedure, then each group divided into three subgroups based on the application of different adhesive systems. There were a total of nine groups as follows. Group 1: Acid + Transbond XT Primer; group 2: Er:YAG (100 mJ, 10 Hz) etching + Transbond XT Primer; group 3: Er:YAG (200 mJ, 10 Hz) etching + Transbond XT Primer; group 4: Transbond Plus self-etching primer (SEP); group 5: Er:YAG (100 mJ, 10 Hz) etching + Transbond Plus SEP; group 6: Er:YAG (200 mJ, 10 Hz) etching + Transbond Plus SEP; group 7: Clearfil Protect Bond; group 8: Er:YAG (100 mJ, 10 Hz) etching + Clearfil Protect Bond; group 9: Er:YAG (200 mJ, 10 Hz) etching + Clearfil Protect Bond. Brackets were bonded with Transbond XT Adhesive Paste in all groups. Teeth to be evaluated for demineralization and SBS were exposed to pH and thermal cyclings, respectively. Then, demineralization samples were scanned with micro-CT to determine lesion depth values. For SBS test, a universal testing machine was used and adhesive remnant was index scored after debonding. Data were analyzed statistically. Results: No significant differences were found among the lesion depth values of the various groups, except for G7 and G8, in which the lowest values were recorded. The lowest SBS values were in G7, whereas the highest were in G9. The differences between the other groups were not significant. Conclusions: Er:YAG laser did not have a positive effect on prevention of enamel demineralization. When two step self-etch adhesive is preferred for bonding brackets, laser etching at 1 W (100 mJ, 10 Hz) is suggested to improve SBS of brackets.